A portrait of one woman outside in the forest with her dog in winter. She is wearing a dress and a fur, Fort Chippewyan. Note on the back reads: ""Sister Edith all dolled up in Arctic White Fox, and good old Dog Rover 1910 at Chippewyan"". (1910)
Women - - Clothing; Fur; Animals; Winter; Nature; Trees